Phonetics in the Brain - Söderström, Pelle (Cambridge University Press, 2024)
This Element outlines how we perceive speech and explores what the auditory system needs to achieve to make this possible. It traces a path through the system and discusses the mechanisms that enable us to perceive speech as a coherent sequence of words. This title is also available as Open Access on Cambridge Core.